Assessment of Heavy Metal Contamination and Ecological Risk in Urban River Sediments: A Case Study from Leyte, Philippines - Abu Bakar Siddique; Abu Sayed Al Helal; Teofanes A. Patindol; Deejay M. Lumanao; Kleer Jeann G. Longatang; Md. Alinur Rahman; Lorene Paula A. Catalvas; Anabella B. Tulin; Molla Rahman Shaibur (Pollutants)
This study evaluated heavy metal (HM) contamination in sediments from the Malbasag River in the Ormoc City port, Leyte, Philippines. A total of thirty sediment samples were collected randomly from ten locations along the river using an Ekman grab sampler. Atomic absorption spectrophotometry revealed HM concentrations in the order of Mn > Zn > Cu > Ni > Pb > Cd. All HMs exceeded their sediment quality guideline (SQG) thresholds except for Mn. Contamination was assessed using indices such as the contamination factor (CF), pollution load index (PLI), geo-accumulation index (Igeo), and enrichment factor (EF). The CF values indicated “moderate to considerable” contamination for Zn, Ni, and Cd, while Cu and Pb showed “very high” contamination levels. The PLI results indicated severe sediment degradation in 20% of samples. The Igeo analysis classified 60% of the samples as “heavily to extremely polluted” for Cd, Cu, and Pb. EF analysis suggested that anthropogenic sources contributed to elevated HM levels, including port activities and agricultural runoff. Ecological risk index (RI) analysis revealed moderate risk in 40% and considerable risk in 20% of sampling locations. Multivariate analyses suggested significant anthropogenic contributions to HM contamination, highlighting the need for further studies to assess the ecological impacts.